Evaluation of flexibility components for improving housing quality using fuzzy TOPSIS method. (March 2019) - Malakouti, Masoud; Faizi, Mohsen; Hosseini, Seyed-Bagher; Norouzian-Maleki, Saeid
Abstract: Flexibility is an important concept in the field of housing with regard to different needs of residents and the need for modifications during the development time. In addition, identifying and implementing the components of flexibility have a significant influence on improving the quality of housing. The objective of the study is to investigate the housing quality indicators in addition to determining the interrelation between these indicators and flexibility components. The components and indicators were extracted using the available literature. Then, the data was collected and the questionnaires were given to the experts of housing design to complete the Delphi procedure. In this study, in order to rank the most crucial components of flexibility, the fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method was performed. The residents' satisfaction level based on flexibility was calculated using the House of Quality (HoQ) matrix. Results revealed that the most influential component of flexibility in quality of housing is accommodating multifunctional spaces and extendibility of spaces. Highlights: The relationship between housing quality indicators and flexibility components is explained. The most effective components of flexibility and their ranking are identified. The housing design requirements are prioritized according to their weights in the HoQ matrix.